(untitled) (Revista Apotheke, 2021)
In this work, experimentation in art/education is discussed as a possibility of formative experiences in the construction of a sensitive daily life. In contemporary times, permeated by an exorbitant number of anesthetic relationships and a crisis of the senses (DUARTE JÚNIOR, 2000), contact with the other becomes increasingly distant. Art emerges as a possibility of experiences without a delimited beginning and end, through experimental practice (DEWEY, 2010). Considering art as a mean of integrating the subject into the city’s space, we retake the memory of the collective proposition ’Divisor’ (1968), by the Brazilian artist Lygia Pape, and the poetic/educational experiences proposed by ’Domingos da Criação’, organized and developed by Frederico de Moraes in the gardens of MAM Rio in 1971. Such productions are marked by the construction of new relationships capable of enhancing the experience in the city through artistic creation, since art is not detached from life, but part and it acts directly on it, in the deweynean molds. The propositions, developed in the Brazilian countercultural period, meet the constant need for a conscious experience of the way we inhabit the city space, modifying the relationships with the urban space, since art and life are not separated.